The Role of Education towards Economic Growth: Evidence from Indonesia - Vita Kartika Sari (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
Education is an important variable in economic activity since competent human resources are originated from good quality education. Human resources are primary input in Neoclassical Production Theory, so that this research mainly aims to estimate the impact of education, labor, and foreign direct investment towards the economic growth in Indonesia. The research data are in the forms of panel data consisting of 34 provinces in Indonesia in the period of 2006 until 2019. The average length of school time is employed as the education variable, the number of labor as the labor variable, and foreign direct investment as capital variable. Based on the estimation results, the selected model for analysis is random effect model. The main findings indicate that education is proved to be significantly positive towards the formation of gross regional domestic product; every 1% increase in education can improve economic output by 2.01%. Labor and foreign direct investment are also proved to be significantly positive towards the gross regional domestic product in Indonesia. Therefore, it requires strategic policies for quality-oriented education improvement and literacy program to all corners of Indonesia since education is a long term investment.